Torulaspora delbrueckii in the brewing process: A new approach to enhance bioflavour and to reduce ethanol content. (June 2016) - Canonico, Laura; Agarbati, Alice; Comitini, Francesca; Ciani, Maurizio
Abstract: Nowadays, consumers require fermented alcoholic beverages with particular and enhanced flavour profiles while avoiding the health concerns due to high ethanol content. Here, the use of Torulaspora delbrueckii was evaluated for beer production, in both pure and in mixed cultures with a Saccharomyces cerevisiae starter strain (US-05). The yeast interactions were also evaluated. In mixed fermentations with S. cerevisiae, the main analytical characters from T. delbrueckii were comparable with those of the S. cerevisiae starter strain, but the beers were characterized by a distinctive overall analytical and aromatic profile. Indeed, there were interactions between S. cerevisiae and T. delbrueckii, with enhanced ethyl hexanoate (0.048 mg l −1 ) and ethyl octaonate (0.014 mg l −1 ) levels at the 1:20 and 1:10 inoculation ratios, respectively; while phenyl ethyl acetate increased in all mix combinations. The presence of T. delbrueckii resulted in reduced β-phenyl ethanol and isoamyl acetate levels, which are responsible for floral and fruity aromas, respectively. Beer produced with T. delbrueckii pure cultures had a low alcohol content (2.66%; v/v), while also showing a particularly analytical and aromatic profile. Highlights: The potential use of a selected Torulaspora delbrueckii strain in the brewing process was evaluated. Mixed fermentation T. delbrueckii / Saccharomyces cerevisiae produced distinctive beer. T. delbrueckii may be proposed to produce a low alcohol beer.